Cedera ACL: Pengalaman Tubuh, Persepsi Diri, dan Rekonstruksi Identitas: ACL Injury: Bodily Experience, Self-Perception, and Identity Reconstruction - Ryawuddin Pakaya Botutihe (Emik : Jurnal Ilmiah Ilmu-Ilmu Sosial, 2026)
Anterior Cruciate Ligament (ACL) injury is one of the most common knee injuries experienced by athletes, particularly in sports involving rapid changes of direction, zigzag movements, and sudden acceleration-deceleration. Existing studies on ACL injury have predominantly focused on biomechanical aspects, causes of injury, and medical recovery, while the subjective experiences of survivors and their impact on self-identity construction remain relatively underexplored, especially within the Indonesian socio-cultural context. This study aims to analyze the lived experiences of ACL survivors after injury and to understand how the rehabilitation process shapes and reconstructs their self-identity. This qualitative research employed a phenomenological approach and was conducted in Makassar. Data were collected through in-depth interviews and participant observation involving eleven informants consisting of ACL survivors, physiotherapists, and family members of survivors, who were purposively selected based on their experiences and involvement in the rehabilitation process. The findings reveal that ACL injury triggers an identity crisis characterized by the loss of social roles as active individuals, the emergence of self-perceptions as vulnerable individuals, and experiences of bodily alienation following surgery. Dependence on others and fear of re-injury further reinforce these identity changes. However, the rehabilitation process functions not only as a space for physical recovery, but also as a social arena in which survivors gradually rebuild self-confidence and reconstruct their identities through environmental support, social interaction, and evolving bodily experiences. This study contributes to the sociology of the body and health studies by demonstrating that injury recovery is also a social process involving the reconstruction of self-meaning, bodily experience, and social relationships in everyday life. It is argued in this article that ACL injury not only affects individuals physically, but also influences how they perceive their bodies and rebuild identity as well as self confidence after experiencing major changes post-surgery.